2016
DOI: 10.1108/jkm-07-2015-0257
|View full text |Cite
|
Sign up to set email alerts
|

The impact of IT-based knowledge management systems on internal venturing and innovation: a structural equation modeling approach to corporate performance

Abstract: Purpose The purpose of this paper is to assess the perceived importance of information technology (IT) as a core factor enabling innovation in knowledge management (KM). The aim is to propose an approach for using the IT tools for KM involved in the design of effective learning applications to help the firms to guide internal venturing development. Design/methodology/approach The research design at the base of the present research has provided a survey which was conducted on a sample consisting of 187 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
199
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(220 citation statements)
references
References 58 publications
4
199
0
3
Order By: Relevance
“…Strategic management research, using a knowledge-based view of the firm, mentions both strategic flexibility (Chen et al 2017;Guo and Cao 2014) and an organization's ability to manage its knowledge internally (Scuotto et al 2017;Del Giudice and Peruta 2016;Ryan et al 2012) as essential for supporting strategic renewal goals (Hughes and Mustafa 2017;Del Giudice et al 2013a, 2013b. These factors are assumed to link synergistically (Chen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Strategic management research, using a knowledge-based view of the firm, mentions both strategic flexibility (Chen et al 2017;Guo and Cao 2014) and an organization's ability to manage its knowledge internally (Scuotto et al 2017;Del Giudice and Peruta 2016;Ryan et al 2012) as essential for supporting strategic renewal goals (Hughes and Mustafa 2017;Del Giudice et al 2013a, 2013b. These factors are assumed to link synergistically (Chen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to [93], it can be concluded that knowledge-oriented leadership can influence KPM and IP. The results obtained from the first research hypothesis are aligned with [94][95][96][97][98][99]. Sustainable balanced performance components grow and develop from knowledge management practices.…”
Section: Discussionmentioning
confidence: 54%
“…In fact, modern firms are increasingly developing and implementing information and communication technologies (ICTs) in several business processes in order to increase their efficiency and innovativeness through new methods of knowledge flow and data information gathering (Giudice and Strub, 2011;Giudice and Peruta, 2016). Therefore, knowledge management can be strongly supported by advanced ICTs.…”
Section: Implementation Of Knowledge Management With An Information Smentioning
confidence: 99%